2014
DOI: 10.1002/pros.22778
|View full text |Cite
|
Sign up to set email alerts
|

MSMB variation and prostate cancer risk: Clues towards a possible fungal etiology

Abstract: BACKGROUND With recent advances in high-throughput sequencing technologies, many prostate cancer risk loci have been identified, including rs10993994, a single nucleotide polymorphism (SNP) located near the MSMB gene. Variant allele (T) carriers of this SNP produce less prostate secretory protein 94 (PSP94), the protein product of MSMB, and have an increased risk of prostate cancer (approximately 25% per T allele), suggesting that PSP94 plays a protective role in prostate carcinogenesis, although the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 86 publications
1
29
0
Order By: Relevance
“…Further analysis on the translated amino acid sequences of these genes showed that they all had a domain that was analogous to the prostatic secretory protein of 94 amino acids (PSP94) based on the topological similarities of the cysteine residues, so we designated them as PSP94-like genes (Fig 6C). It was reported that the PSP94 genes in vertebrates underwent rapid evolution, which resulted in an improvement of their functions in a wide range of biological activities, such as inhibition of tumor growth [46], activation of immunity [47], and mesoderm formation [48]. Taken together, their specific arrangement pattern and distinguished expression profiles strongly suggested that the PSP94-like genes might play a vital role in the regenerative abilities of A .…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis on the translated amino acid sequences of these genes showed that they all had a domain that was analogous to the prostatic secretory protein of 94 amino acids (PSP94) based on the topological similarities of the cysteine residues, so we designated them as PSP94-like genes (Fig 6C). It was reported that the PSP94 genes in vertebrates underwent rapid evolution, which resulted in an improvement of their functions in a wide range of biological activities, such as inhibition of tumor growth [46], activation of immunity [47], and mesoderm formation [48]. Taken together, their specific arrangement pattern and distinguished expression profiles strongly suggested that the PSP94-like genes might play a vital role in the regenerative abilities of A .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, psoriasin possesses a histidine residue in its C-terminal region [127] similar to amoebapore A [82] and based on these similarities, it can be speculated that the enhanced action of psoriasin against B. megaterium at low pH may involve a histidine mediated increased ability for pore formation and oligomerisation. β-microseminoprotein (MSP), also named as PSP-94, is a human protein that is believed to have a protective role in prostate carcinogenesis due to its ability to suppress the growth of tumors although more recent studies have suggested that MSP may protect against prostate cancer by inhibiting fungal infection in this genital region [134,135]. This suggestion was primarily based on recent work, which showed that the acid conditions of the vagina promoted the ability of MSP in post coital seminal plasma to kill Candidia albicans .…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…Fungal infections of the prostate are rare and primarily occur in immunocompromised patients. Sutcliffe et al 19 suggested that to screen for fungi in prostate specimens and explore their mechanism of action, future research should consider using rapidly advancing molecular techniques. Therefore, we used high‐throughput next‐generation sequencing technology to detect the gene sequences of all eukaryotic microorganisms in the specimens.…”
Section: Discussionmentioning
confidence: 99%